Edge Steganography for Binary Image - Hongxia Wang; Gouxi Chen; Meng Zhang (Institute of Advanced Engineering and Science, 2013)
In order to improve the steganographic robustness of the algorithm in binary images, suppose an new steganographic method which deals with the edge of the binary image using mathematical morphology and combines F5 encoding method to embedded information. Marginalization and reconstruction on binary image by dilation and erosion operations, and tag blocks that can embed information to. Finally embed secret information using F5 algorithm. Through experiments and analysis it comes out the steganographic robustness of the algorithm can be enhanced, and have a small changes on the carrier image quality after embedding information, and also has a good embedding capacity. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2557